The Impact of digitization on the religious sphere: televangelism as an example - Shaimma El Naggar (IAIN Salatiga, 2014)
Over the past few decades, televangelism has emerged as one important media phenomenon, inter alia, among Muslim communities. As a phenomenon, televangelism is interesting in many respects; it is a manifestation of the phenomenon of